20-Week follow-up of hepatic steatosis installation and liver mitochondrial structure and activity and their interrelation in rats fed a high-fat–high-fructose diet. Issue 4 (2nd March 2018) - Fouret, Gilles; Gaillet, Sylvie; Lecomte, Jerome; Bonafos, Beatrice; Djohan, Ferdinand; Barea, Bruno; Badia, Eric; Coudray, Charles; Feillet-Coudray, Christine
Abstract: The incidence of obesity and its metabolic complications are rapidly increasing and become a major public health issue. This trend is associated with an increase in the prevalence of non-alcoholic fatty liver disease (NAFLD), insulin resistance and diabetes. The sequence of events leading to NAFLD progression and mitochondrial dysfunction and their interrelation remains to be elucidated. This study aimed to explore the installation and progression of NAFLD and its association with the liver mitochondrial structure and activity changes in rats fed an obesogenic diet up to 20 weeks. Male Wistar rats were fed either a standard or high-fat–high-fructose (HFHFR) diet and killed on 4, 8, 12, 16 and 20 weeks of diet intake. Rats fed the HFHFR diet developed mildly overweight, associated with increased adipose tissue weight, hepatic steatosis, hyperglycaemia and hyperinsulinaemia after 8 weeks of HFHFR diet. Hepatic steatosis and many biochemical modifications plateaued at 8–12 weeks of HFHFR diet with slight amelioration afterwards. Interestingly, several biochemical and physiological parameters of mitochondrial function, as well as its phospholipid composition, in particular cardiolipin content, were tightly related to hepatic steatosis installation. These results showed once again the interrelation between hepatic steatosis development and mitochondrial activity alterations without being able to say whether the mitochondrial alterations preceded or followed the installation/progression of hepatic steatosis. Because both hepatic steatosis and mitochondrial alterations occurred as early as 4 weeks of diet, future studies should consider these four 1st weeks to reveal the exact interconnection between these major consequences of obesogenic diet intake.